State, Custom, and Islamic Law in Aceh: Minor Dispute Resolution in the Perspective of Legal Pluralism - Ramli, Misran; Rijal, Syamsul; Surya, Reni; Malika, Irhamni (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This paper aims to examine the juridical basis for the application of Acehnese customary law, the mediation mechanism of Aceh Tamiang customary law in resolving minor disputes. The study of this paper used empirical research methods, using the theory of legal pluralism. Data were collected by means of in-depth interview and document study. Interviews were conducted with customary stakeholders, while the documents analysed were news of peace events in Aceh Tamiang. The findings reveal that the juridical basis for resolving minor disputes is based on the Law, the Qanun, and the Joint Decree between the Governor, the Aceh Regional Police Chief, and the Chair of the Aceh Customary Council (Majelis Adat Aceh). In Aceh Tamiang, the customary law mediation mechanism in gampong (village) and mukim (township) customary justice is generally carried out by reporting, requiring the presence of the parties to the dispute as well as the witnesses, and being open to the public. However, exception occurs for special disputes, in which according to custom and propriety must not be open to the public, and there is no charge whatsoever. Among the minor disputes that have been successfully resolved through gampong customary courts are domestic violence, inheritance disputes, land ownership, the construction of Telkomsel towers, and traffic accidents. The resolution of minor disputes in Aceh Tamiang from the perspective of legal pluralism has been carried out harmoniously and correlates between state law, customary law, and Islamic law. State law provides an opportunity for customary law to resolve minor disputes, and if it is not successful, then state law will take over. Further, dispute resolution in customary law is also in accordance with the values of Islamic law, which also prioritizes peace or al-sulh. This corresponds to the Acehnese proverb that states “adat ngen hukom lage zat ngen sifeut” which means the relationship between customary law and Islamic law is like a substance with its inseparable properties.